Modern approaches to rehabilitation of military men with a gun-shot polystructural woundings of upper extremity - I. V. Roy; N. О. Borzykh; L. D. Каtіukova; О. V. Borzykh (Клінічна хірургія, 2019)
Objective. To improve the results of treatment in the patients with polystructural gun-shot woundings of the upper extremity, using elaboration and individualization of the rehabilitation program, depending on the trauma severity degree.